Systematic Literature Review on Presbyacusis - Donny Haryxon; Sri Marhaeni (LPPM Universitas Abdurrab, 2024)
Presbyacusis, or age-related hearing loss, is a prevalent condition among the elderly, characterized by a gradual decline in hearing sensitivity, particularly for high-frequency sounds. This systematic literature review synthesizes current research on the epidemiology, pathophysiology, risk factors, diagnosis, and management of presbyacusis. The review aims to provide a comprehensive understanding of the condition, its impact on quality of life, and the effectiveness of various interventions.Presbyacusis, age-related hearing loss